1999
DOI: 10.1161/01.hyp.33.4.1025
|View full text |Cite
|
Sign up to set email alerts
|

Local Renin-Angiotensin System Is Involved in K + -Induced Aldosterone Secretion from Human Adrenocortical NCI-H295 Cells

Abstract: Abstract-NCI-H295, a human adrenocarcinoma cell line, has been proposed as a model system to define the role of the renin-angiotensin system in the regulation of aldosterone production in humans. Because the precise cellular localization of the components of the renin-angiotensin system in human adrenal cortical cells remains unclear, we investigated their localization in this defined cell system. NCI-H295 cells expressed both angiotensinogen and renin as shown by reverse transcriptase polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…By contrast, steroidogenesis of R cells is reported to be regulated by AngII , potassium , Pezzi et al 1996, Hilbers et al 1999, and ACTH , Staels et al 1993, Mountjoy et al 1994. These investigators observed that the responsiveness of R cells is highly dependent on growth conditions .…”
Section: Steroid Production In a And R Cells After Stimulation With Amentioning
confidence: 99%
“…By contrast, steroidogenesis of R cells is reported to be regulated by AngII , potassium , Pezzi et al 1996, Hilbers et al 1999, and ACTH , Staels et al 1993, Mountjoy et al 1994. These investigators observed that the responsiveness of R cells is highly dependent on growth conditions .…”
Section: Steroid Production In a And R Cells After Stimulation With Amentioning
confidence: 99%
“…This idea is supported by evidence that adrenal renin expression increases in response to small and transient increases of serum potassium levels; this increase has been shown to contribute to the rise in aldosterone production (10,26). Furthermore, also in human NCI-H295 cells, a local renin-angiotensin system is involved in potassium-induced aldosterone secretion (14).…”
Section: Discussionmentioning
confidence: 89%
“…The second is that the local expression of adrenal renin is required for normal ZG function (7,9,10,14,16,26,28,29,31). One of the theories is that local generation of adrenal ANG II mediates the ZG response to increases in potassium and that this is mediated by AT 1 -type angiotensin receptors (14,26,29).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been known for decades that the adrenal cortex also expresses a local RAAS that operates independently of the renal RAAS (2,7,9,14,16,26,28). One theory is that adrenal renin-generated ANG II mediates the ZG response to increases in plasma potassium, and this is mediated by expression of the angiotensin AT 1 receptor (5,9,14,26,29).The development of the renin knockout (KO) rat provides a unique opportunity to begin to evaluate these phenomena (13).In the current study, we have begun this process by evaluating the aldosterone and corticosterone response to cAMP in vitro by the measurement of adrenal steroidogenic gene expression and by morphological examination of adrenal zonation by immunohistochemical analysis of the two major late-pathway steroidogenic enzymes: P450aldo (CYP11B2) that mediates the conversion of corticosterone to aldosterone in the ZG and P45011␤ (CYP11B1) that mediates corticosterone production in the zona fasciculata/reticularis (ZFR) (8). …”
mentioning
confidence: 99%
See 1 more Smart Citation